The characteristics and treatment needs of fire setters with intellectual disability: descriptive data and comparisons between offence type. Issue 4 (18th October 2019) - Curtis, Ashlee; McVilly, Keith R.; Day, Andrew; Lindsay, William R.; Taylor, John L.; Hogue, Todd E.
Abstract : Purpose: Fire setters who have an intellectual disability (ID) are often identified as posing a particular danger to the community although relatively little is known about their characteristics, treatment and support needs. The paper aims to discuss this issue. Design/methodology/approach: This study describes the characteristics of 134 residents of low, medium and high security ID facilities in the UK who have either an index offence of arson, a violent index offence or a sexual index offence. Findings: Index arson offenders who had an ID had multiple prior convictions, a history of violent offending and a high likelihood of having a comorbid mental disorder. There were many shared characteristics across the three groups. Practical implications: The current study suggests that offenders who have ID who set fires have treatment needs that are similar to those of violent and sex offenders. It follows that fire setters who have an ID may also benefit from participating in more established offending behaviour treatment programs, such as cognitive behaviour therapy programs, developed for other types of offender. Originality/value: This study is one of the few which has investigated the characteristics and treatment needs of persons who have an ID who set fires. In particular, it is one of the first to compare the characteristics and treatment needs for persons with ID who set fires, to those who have committed violent and sexual offences.